Drivers of advanced stage at breast cancer diagnosis in the multicountry African breast cancer – disparities in outcomes (ABC‐DO) study. Issue 8 (23rd December 2017) - McKenzie, Fiona; Zietsman, Annelle; Galukande, Moses; Anele, Angelica; Adisa, Charles; Parham, Groesbeck; Pinder, Leeya; Cubasch, Herbert; Joffe, Maureen; Kidaaga, Frederick; Lukande, Robert; Offiah, Awa U.; et al.
Abstract : Breast cancer (BC) survival rates in sub‐Saharan Africa (SSA) are low in part due to advanced stage at diagnosis. As one component of a study of the entire journey of SSA women with BC, we aimed to identify shared and setting‐specific drivers of advanced stage BC. Women newly diagnosed in the multicountry African Breast Cancer–Disparities in Outcomes (ABC‐DO) study completed a baseline interview and their stage information was extracted from medical records. Ordinal logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for advanced stage (I, II, III, IV) in relation to individual woman‐level, referral and biological factors. A total of 1795 women were included from Nigeria, Uganda, Zambia, and the multiracial populations of Namibia and South Africa, 1091 of whom (61%) were stage III/IV. Stage was lower in women with greater BC knowledge (OR 0.77 (95% CI: 0.70, 0.85) per point on a 6 point scale). More advanced stage was associated with being black (4.00 (2.79, 5.74)), having attended <secondary education (1.75 (1.42, 2.16)), having never heard of BC (1.64 (1.31, 2.06)), an unskilled job (1.77 (1.43, 2.20)) and pregnancy in the past 3 years (30% of ≤45 year olds) (1.63 (1.15, 2.31)), and were mediated through delays to diagnosis: symptom duration of ≥ 1 year (OR 2.47 (1.93, 3.15)). These findings provide further evidence that late‐stage BC in SSA is largely attributed to modifiable factors and strategies to improve BC education and awareness in women and the health system should be intensified. Abstract : What's new? Breast cancer (BC) patients in sub‐Saharan Africa (SSA) tend to have poor prognoses and low survival rates. This is largely because the majority of cases are not diagnosed until the disease has reached an advanced stage. In this study, the authors found that delayed diagnosis is associated with several modifiable factors, including limited schooling, low‐wage jobs, and lack of awareness of BC. With incidence rates of BC steadily climbing in SSA, it is urgent that efforts to improve disease‐specific education and awareness both among women and throughout the healthcare system be intensified.